“Au bal des actifs”: L’éthique du futur pour penser le travail de demain (TEST Ticontre. Theory Text Translation, 2022)
What will tomorrow's world of work look like? This article describes and analyses the tension at work in the science fiction collection Au bal des actifs. Demain le travail. Built on two opposite, albeit porous, horizons, the volume invites us to reflect successively on two founding assumptions : on the one hand, the end of work linked to the automation of the various sectors of employment; on the other, the professional world dominated by “bullshit jobs”. In doing so, it serves as a criticism of the current mutations.